The Effectiveness Green Spinach Boiled and Fe Tablets on Increasing Hb Levels in 3rd Pregnant Women - Simanjuntak, Farida Mentalina; Fatimah, Anita Zul; Siantar, Rupdi Lumban (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2024)
If anemia in pregnant women is not treated properly, it will be a contributor to maternal death. Based on data sources from the West Java Health Service in Bekasi Regency, in 2020 there were 835 anemia in pregnant women. One way to increase hemoglobin is with pharmacological and non-pharmacological therapy, namely consuming green spinach and Fe tablets.Analyzing the effectiveness of giving green spinach decoction and Fe tablets on increasing Hb levels in pregnant women in 2024.Research methods: Using a pre-experimental research design, one group pretest posttest design, sample size of 20 people, total sampling technique, research variables: 450 gr green spinach decoction given once a day for 7 days and Fe tablets once a day for 7 days. Data analysis: Univariate, Bivariate using Wilcoxon. There is effectiveness of giving boiled green spinach using the Wilcoxon test (p value = 0.046 < P 0.05), which means that giving boiled green spinach to pregnant women has an effect on increasing Hb levels and giving FE tablets is more effective in increasing HB with the results of the Wilcoxon test (p value = 0.008 <P 0.05).Conclusion: Fe tablets are more effective in increasing the Hb of pregnant wome Suggestion: It is hoped that future researchers will carry out similar research on different targets and variables.Anemia in pregnancy is a contributor to maternal and infant mortality. Based on data from the Bekasi Health Service in 2020,835 pregnant women experienced anemia in pregnant women. Efforts to increase hemoglobin levels can be done by pharmacological and non-pharmacological methods, namely consuming Fe tablets regularly, but one way to meet iron needs naturally can be done by consuming boiled green spinach and Fe tablets.Analyzing the effectiveness of giving green spinach decoction and Fe tablets on increasing Hb levels in pregnant women in 2024Analyzing the effectiveness of giving green spinach decoction and Fe tablets on increasing Hb levels in pregnant women.Research methods: Using a pre-experimental research design, one group pretest posttest design, sample size of 20 people, total sampling technique, research variables: 450 gr green spinach decoction given once a day for 7 days and Fe Pre-experimental research design, one group pretest posttest design, population of all pregnant women in the third trimester. Total sampling technique, research variables: boiled green spinach and Fetablets once a day for 7 days. HB measuring instrument research instrument, checklist sheet. Data analysis: Univariate, Bivariate using Wilcoxon. There is effectiveness of giving boiled green spinach using the Wilcoxon test (p value = 0.046 < P 0.05), which means that giving boiled green spinach to pregnant women has an effect on increasing Hb levels and giving FE tablets is more effective in increasing HB with the results of the Wilcoxon test (p value = 0.008 <P 0.05).